Magic in Literature and Law: Depictions of Magic in the Christian Elite Latin Writing Culture of the Insular World as Evidenced in Hagiography, Penitential Literature, and Synod Canons Before c.800 - Korth, Jeremy Michael (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2025)
Before c. 800 C.E. the Christian elite of the insular world produced two ecclesiastical corpora of Latin texts that each show strong degrees of intertextuality within each corpus and contain within them insights into the authors' thoughts on magic. The first of these is hagiographical literature, comprising nine vitae of six saints: two lives of St Brigit, two accounts of St Patrick, one life of St Columba, two of St Cuthbert, a life of Pope Gregory the Great, and an account of St Wilfrid. Not only were these texts each composed within a short time of one another, but they also exist in dialogue together. The second is a collection of related ecclesiastical legal texts, containing a number of records of the canons of synods as well as a plethora of penitential literature. By analysing these texts through close reading of passages containing vocabulary that indicates magic, this thesis synthesises the ideas about and conceptions of magic contained therein, bringing a greater understanding of the thought-world of the authors of the texts. This thesis has established three strains of thought regarding magic in the hagiographical material. The first of these is one that sees magical beliefs and practices as having been once a proper and ordained part of God's plan that became unnecessary following the arrival of Christianity. The second is one that views all magic as complete and inherently evil and that those who practice it can either: 1) be beyond redemption and deserving of death in order to clear the way for proper practice of Christian religion; or 2) leave their beliefs and practices behind and be converted to join the church. The final strain of thought views magic as being evil, but mostly for its threat to the political position and orthodox teachings of the church, but holds that its practitioners can be converted, redeemed, and possibly coopted into the church as priests and other ecclesiastical leaders. The legal sources present two concerns with the belief in and practice of magic. The first of these arises out of the paternalistic and pastoral nature of penitential literature, and deals with the danger that magical belief and practice presents to the souls of practitioners and those around them. The second of these is a concern for the socio-political power of the church and its ability to influence the people of the region, the ways in which unorthodox and un-Christian magical practices can subvert the teachings of the church and undermine its position and authority, and focuses on curtailing in the belief in and influence of magical practitioners in the Christian community. In so doing, this thesis addresses a current hole in the scholarship on magic of the early medieval insular world. Most of the scholarship on early medieval insular magic is focused on either the reconstruction of pre-Christian beliefs and traditions from Christianised myths and Christian accounts of pre-Christian history, on magic as it exists in the vernacular texts of the region, on creating or refining modern philosophical definitions of magic that are then applied to the texts created by the peoples of the past, or on texts that have been deemed inherently magical such as books of charms. While these are worthy academic ventures, they leave a noticeable gap consisting of the Christian ecclesiasts' understandings of, ideas about, and attitudes towards those things which they deemed magical for themselves. This thesis - through its analysis of these two corpora - provides insight that can be used to further scholarly understanding of the way that the Christian elite of the early medieval insular world related to their own mythic past and those people in their present whom they believed to be engaged or believing in practices that they considered to be magical in nature. Finally, it also lays the groundwork for future scholarship on magic following the methodology established in this thesis, whether that be magic in other Latin texts or vernacular texts of the same place and time, or the texts of other cultures.
APPROVED
Keywords: History of Magic; Medieval Magic; Early Medieval Magic